Conceptual Design for an Eye-Tracking Experiment on Formula Linebreaking - Kohlhase, Andrea; Kohlhase, Michael (CEUR Workshop Proceedings, 2022)
Traditionally, technical documents have been designed for print delivery in letter, A4, or similar sizes. Even the change to digital delivery using PDF has not changed the basic layout strategy and desktop screens can cope well. With the advent of mobile connected devices, it becomes natural to read technical documents (like everything else) e.g. on smartphones, which may demand other layout tradeoffs. The document components most affected by this are diagrams and formulae, which - unlike text - cannot simply be reflowed to a new screen size. In this paper, we discuss an experimental study design that helps the investigation of the effect of linebreaking in mathematical formulae for reading efficiency using eye-tracking experiments.
CRIS-Team Scopus Importer:2024-12-16
Keywords: tbd